Upgraded curriculum? An analysis of knowledge boundaries in teaching under the Swedish subject-based curriculum*. Issue 3 (3rd July 2018) - Adolfsson, Carl-Henrik
ABSTRACT: This article offers a contribution to the current debate about knowledge and the curriculum, especially initiated by social realist writers. The enacted Swedish subject-based curriculum for compulsory schooling is examined and is also used as a significant case with the aim of discussing practical implications of social realist claims regarding knowledge and the curriculum. Video-recorded lessons from grade six in six different Swedish schools, in combination with teacher interviews, are explored within the scope of a curriculum theory framework with the purpose of illuminating dominant patterns of knowledge boundaries and knowledge conceptions. The study shows how the Swedish subject-based curriculum frames teaching in a direction where a disciplinary knowledge conception with fixed knowledge boundaries predominates over other knowledge forms. The subject-based curriculum also appears to produce an 'overloading' of content, which implies that pupils' questions and experiences are avoided and dismissed in the teaching practice.